1997
DOI: 10.1017/s0031182096008062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of human cystic hydatid cases from Poland: identification of a new genotypic group (G9) of Echinococcus granulosus

Abstract: We have used nuclear (ribosomal ITS1) and mitochondrial (ND1) sequences to characterize human and pig isolates of Echinococcus granulosus collected by fine needle aspiration biopsy (FNAB) in Poland. The data indicate clearly that the Polish patients were not infected with the common sheep strain (G1 genotype) of E. granulosus, normally associated with human cystic hydatid infection. Instead, the hydatid parasite infecting the Polish patients shares very similar ND1 sequence with the previously characterized pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 7 publications
2
70
0
1
Order By: Relevance
“…The presence of E. granulosus genotypes G2, G5, G6 and G9 in humans was confirmed in Argentina and Poland (Guarnera et al, 2004;Rosenzvit et al, 1999;Scott et al, 1997), while in China previous studies from different areas revealed that human infections were caused by the G1 genotype (McManus et al, 1994;Yang et al, 2005;Zhang et al, 1998). However, in Xinjiang Uygur autonomous region the camel strain (G6) was also recently shown to infect humans (Bart et al, 2006).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The presence of E. granulosus genotypes G2, G5, G6 and G9 in humans was confirmed in Argentina and Poland (Guarnera et al, 2004;Rosenzvit et al, 1999;Scott et al, 1997), while in China previous studies from different areas revealed that human infections were caused by the G1 genotype (McManus et al, 1994;Yang et al, 2005;Zhang et al, 1998). However, in Xinjiang Uygur autonomous region the camel strain (G6) was also recently shown to infect humans (Bart et al, 2006).…”
Section: Discussionmentioning
confidence: 90%
“…Substantial genetic diversity of E. granulosus has led to the description of 10 genotypes (G1-10) (Bowles et al, 1992(Bowles et al, , 1995Bowles and McManus, 1993;Lavikainen et al, 2003;Nakao et al, 2007;Scott et al, 1997), and the G1 genotype has been proved to be cosmopolitan in its distribution and the major cause of human infection (McManus, 2002;Thompson and McManus, 2001). In China, previous genotypic analysis indicated the pathogenicity of the G6 genotype (dog/camel) in humans in Xinjiang autonomous region (Bart et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic PCR-amplified ITS1 and PCR-ITS1 RFLP banding patterns were produced when samples within Echinococcus species and strain group were analysed. The approach proved rapid and, although its usefulness has been questioned (Kedra et al 1999), it has proved applicable and reliable in the hands of a number of researchers for the identification of newly collected isolates and for the investigation of E. granulosus transmission patterns where strains occur sympatrically Wachira et al 1993 ;Bowles, Blair & McManus, 1994 ;Scott et al 1997 ;Rosenzvit et al 1999 ;Snabel et al 2000 ;Gonzalez et al 2002).…”
Section: Rflp/rapd Analysismentioning
confidence: 99%
“…Nuclear ribosomal ITS1-PCR-RFLP patterns and nad1 sequences were compared for human isolates of Polish origin (Scott et al 1997) collected by fine needle aspiration biopsy (FNAB). This is a procedure that, along with ultrasonography, allows differential diagnosis of suspected hepatic cysts in the liver and permits collection of parasite material for analysis from patients residing in areas where hydatid disease is relatively uncommon (Stefaniak & Lemke, 1995).…”
Section: Molecular Genetic Analysis Of Human Cystic Echinococcosis Camentioning
confidence: 99%
See 1 more Smart Citation